TRANSNATIONAL FEELINGS: DIGITAL AFFECT AS A GLOBAL ANALYTIC - Jaber, Heather; Kraidy, Marwan; Al-Ghazzi, Omar; Zidani, Sulafa (AoIR Selected Papers of Internet Research, 2021)
This panel examines the role of affect in transnational digital media, offering fine-grained analyses of online communities and media artifacts which contend with and carve out contested futures. In doing so, it offers digital affect as an analytic for contending with interdependent realities. Through qualitative interviews, close readings, and textual analyses, these projects engage in a range of approaches to trace the digital affects which circulate transnationally. They examine the World Economic Forum as a transnational spectacle of justice, the promotional materials and the recoding work of extremist groups like the so-called “Islamic State,” online communities which suture continuities between Al-Andalus and an emerging Arab Muslim identity, and global meme-makers who engage in expression through playful but also puncturing forms of critique. Through these case studies, the panel examines the power of particular affects—like nostalgia, fear, shame, and zanaakha, a kitschy humor of the times—and the particular power of affects—to bind and polarize communities, to identify transnational structures of feeling, and to reshape the political present by feeling history differently. By turning to these spaces, these projects make the case for careful, contextualized approaches to affect and digital media in order to mine their political power.